Analisis Kecurangan Terhadap Praktik Laporan Keuangan PT. Asuransi Jiwasraya (Persero) Di BEI Tahun 2017-2019 - Rahmiyati; Cantika; Nanda Ulana Simanjuntak (Journal of Applied Accounting And Business, 2021)
This research discusses fraud against the financial reporting practices of PT Asuransi Jiwasraya (Persero) 2017-2019, where the information presented in the financial statements must not have the interest of one party because it will harm the other party. This study aims to determine the occurrence of fraud in the practice of financial reporting at PT Asuransi Jiwasraya (Persero) in 2017-2019. This study uses secondary data. The population in this study is the company PT Asuransi Jiwasraya (Persero) which is listed on the Indonesia Stock Exchange in 2017-2019. This research uses descriptive quantitative method with descriptive statistical analysis tools and literature study collection methods. The results show that the income at PT Asuransi Jiwasraya (Persero) in 2017-2019 has increased quite significantly while the expenses for PT Asuransi Jiwasraya have also increased but overall it is very significant. This shows that the income at PT Asuransi Jiwasraya (Persero) has increased significantly when their expenses are high. In the case of this financial statement, the company should as much as possible reduce the expenses on the company so that they are more focused on company revenue.